Molecular Docking Senyawa Yang Berpotensi Sebagai Antikanker Payudara: Literature Review - Anisa Fauziah; Adelia Fatharani; Cindhy Maulida Nurawaliah; Faizal Auladi Rivianto; Irene Virda Sakina; Marsah Rahmawati; Lina Nurfadhila (Journal of Pharmaceutical and Sciences, 2023)
Cancer is a degenerative disease that has claimed many victims. Currently breast cancer is the second most common cancer that causes death after lung cancer and is the most common cancer suffered by women. Treatment of breast cancer is generally done with chemotherapy, radiotherapy, hormone therapy and surgery. Several synthetic drugs have been used to inhibit the growth of cancer cells. However, these drugs have dangerous side effects for the body so other alternatives are needed, including developing drugs derived from plants. To predict the activity of compounds from plants that have potential as anti-breast cancer, the molecular docking method was used. This review aims to inform compounds that have the potential as anti-breast cancer based on the results of molecular docking. The research method used was a literature study of 15 journals searched on the Google Scholar and Google databases related to molecular docking of breast anticancer compounds. The results of the review show that several compounds have the potential to inhibit breast cancer receptors including mangiferin compounds which are the best at inhibiting HER-2 receptors, quercetin glycoside compounds which are the best at inhibiting Bcl-2 receptors, quinine compounds which are the best at inhibiting ER-α receptors, compounds 6,7 -dihydro-17-hydroxyerisotrin is the best at inhibiting EGFR receptors, curcumin compounds are the best at inhibiting COX-2 receptors and eugenol compounds are the best at inhibiting ER-β receptors.